EFFECTIVENESS OF ANTHOCYANIN AS A HEPATOPROTECTOR: A SYSTEMATIC LITERATURE REVIEW - Amanda Putri, Khairunnisa Rizqika; Lusiana, Evi; Theodorus; Rosdah, Ayeshah Augusta; Harahap, Debby Handayati; Larasati, Veny (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Exposure to free radicals can cause hepatotoxicity in liver cells. Hepatoprotectors are needed to prevent free radicals. The flavonoid group anthocyanin compounds, which give many plants purple, blue, and red colors, have antioxidant activity as hepatoprotectors. This study uses a systematic literature review to review the effectiveness of various plants containing anthocyanins as hepatoprotectors. Articles were searched using Google Scholar, PubMed, and NCBI with keywords such as